2019
DOI: 10.2478/hukin-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Relationship Between Leg Bone Length and Running Performance in Well‐Trained Endurance Runners

Abstract: The present study aimed to determine the relationship between leg bone length and running performance in well-trained endurance runners. The lengths of the leg bones in 42 male endurance runners (age: 20.0 ± 1.0 years, body height: 169.6 ± 5.6 cm, body mass: 56.4 ± 5.1 kg, personal best 5000-m race time: 14 min 59 s ± 28 s) were measured using magnetic resonance imaging. The lengths of the femur and tibia were calculated to assess the upper and lower leg lengths, respectively. The total length of the femur + t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 14 publications
3
16
3
Order By: Relevance
“…We previously reported that MRI-measured leg bone length correlated with running performance in endurance runners [14]. By contrast, in the present study, we found that absolute and relative leg lengths of the femur and tibia did not correlate with sprint performance in both 100-m and 400-m sprinters.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We previously reported that MRI-measured leg bone length correlated with running performance in endurance runners [14]. By contrast, in the present study, we found that absolute and relative leg lengths of the femur and tibia did not correlate with sprint performance in both 100-m and 400-m sprinters.…”
Section: Discussioncontrasting
confidence: 99%
“…The intraclass correlation coefficient for the two measurements in all subjects was 1.000 (95% CI, 0.999-1.000) for the femoral length and 0.999 (95% CI, 0.999-1.000) for the tibial length. Moreover, our previous study has reported high reproducibility of the leg bone length measurements on 2 separate days [14]. Furthermore, in the present study, we examined the relationship between the lengths of the tibia and fibula to ensure the validity of the tibial length as the lower leg length.…”
Section: Mri Measurementsmentioning
confidence: 89%
See 3 more Smart Citations